SNPs in LncRNA genes are associated with non‐small cell lung cancer in a Chinese population. Issue 4 (13th April 2019) - Wang, Ruoyang; Feng, Nannan; Wang, Yu; Gao, Sumeng; Zhang, Fangfang; Qian, Ying; Gao, Ming; Yu, Herbert; Zhou, Baosen; Qian, Biyun
Abstract : Background: It has indicated that single nuclear polymorphisms (SNPs) in the regions encoding non‐coding transcripts are associated with lung cancer susceptibility. In a previous microarray study, we identified 13 differentially expressed long non‐coding RNAs (lncRNAs) in non‐small cell lung cancer (NSCLC) and associations of SNPs in these lncRNA genes with lung cancer were unknown. We conducted a case‐control study to address this issue. Methods: Using the TaqMan method, we genotyped 17 SNPs located in the 13 lncRNA genes in 1294 cases with NSCLC and 1729 healthy controls. Unconditional logistic regression and Cox proportional hazards regression were used to analyze the associations of these SNPs with NSCLC risk and patient survival, respectively. These analyses were also repeated in subgroups of cases and controls stratified by gender, age group, smoking status, disease stage, and histological type. Results: We identified three SNPs associated with NSCLC risk. For SNP rs498238, CC genotype was associated with lower risk compared to TT genotype (adjusted OR = 0.33, 95%CI: 0.11‐0.97, P  = 0.043). For rs16901995, CT/TT genotypes were associated with lower risk compared to CC genotype in non‐smokers (adjusted OR = 0.78, 95%CI: 0.62‐0.98, P  = 0.035). Variant genotypes in rs219741 were associated with NSCLC risk in young patients, and the adjusted OR was 1.47 (95%CI: 1.03‐2.10, P  = 0.033) when compared to the wild genotype. No SNPs were found to be associated with patient overall survival in the study. Conclusion: The study suggests that some genetic polymorphisms in the lncRNA genes may influence the risk of NSCLC among Chinese.